Productivity Efforts in Bais Bay Basin - Ablan, Christopher A.; Villar, Nelson C.; Monte de Ramos, Rowel A. (Silliman Journal, 2023)
This report presents a narrative description of the activities during the first year of the project (November 1991 to October 1992), the strategies used and their underpin-nings, and finally our reflections about the project goals and the strategies used.